Application of NiOx thin films as p‐type emitter layer in heterojunction solar cells. Issue 10 (13th September 2016) - Menchini, Francesca; Grilli, Maria Luisa; Dikonimos, Theodoros; Mittiga, Alberto; Serenelli, Luca; Salza, Enrico; Chierchia, Rosa; Tucci, Mario
Abstract: Non‐stoichiometric nickel oxide (NiOx ) is attracting growing attention due to its characteristics of p‐type transparent conductive layer and to the possibility to tailor its optical and electrical properties. NiOx could also be employed as the electron blocking layer in silicon‐based heterojunction solar cells. However, at present not much work has been done in this direction. In this paper we investigate the optoelectronic characteristics of NiOx thin films and demonstrate the usability of NiOx as emitter layer in silicon based heterostructure solar cells due to its hole collection selectivity. Test heterojunctions show a rectifying behaviour, even if their characteristics are still limited by the density of defects at the c‐Si/NiOx interface, as deduced by comparing the experimental results with numerical simulations. This suggests that the quality of the interface between NiOx and c‐Si needs to be improved, either by optimizing the deposition process of NiOx or by depositing a buffer layer able to carefully passivate the silicon surface and helpfully allow the growth of oxide layer. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)